Finitely represented dyadic sets and their multielementary representations - Belousov, K.I.; Nazarova, L.A.; Roiter, A.V. (Український математичний журнал, 1997)
We obtain the direct reduction of representations of a dyadic set S such that |Ind C(S)| < ∞ to the bipartite case. Отримано пряме зведення зображень діадичної множини S, що задовольняє |Ind C(S)| < ∞ до бікомпонентного випадку.